2013
DOI: 10.1186/1471-2407-13-540
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin is a prognostic biomarker in non-small cell lung cancer

Abstract: BackgroundIn a previously published report we characterized the expression of the metastasis-associated proteins S100A4, osteopontin (OPN) and ephrin-A1 in a prospectively collected panel of non-small cell lung cancer (NSCLC) tumors. The aim of the present follow-up study was to investigate the prognostic impact of these potential biomarkers in the same patient cohort. In addition, circulating serum levels of OPN were measured and single nucleotide polymorphisms (SNP) in the -443 position of the OPN promoter w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 30 publications
7
35
0
8
Order By: Relevance
“…In gastric cancer (Tang et al 2008), a similar importance was found between osteopontin expression and clinical stages, nodal metastasis, and distant metastasis. Emerging data support a role for osteopontin as a potential prognostic factor in various human tumors, including non-small cell cancer (Rud et al 2013), hepatocellular carcinoma (Zhang et al 2012), and prostate cancer (Forootan et al 2006). However, the correlation between osteopontin expression and survival is controversial in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer (Tang et al 2008), a similar importance was found between osteopontin expression and clinical stages, nodal metastasis, and distant metastasis. Emerging data support a role for osteopontin as a potential prognostic factor in various human tumors, including non-small cell cancer (Rud et al 2013), hepatocellular carcinoma (Zhang et al 2012), and prostate cancer (Forootan et al 2006). However, the correlation between osteopontin expression and survival is controversial in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…An association of multifocal brain involvement with inferior outcome has previously been reported [37,38]. Moreover, a correlation of increased circulating OPN levels and increased OPN expression by tumour cells with an unfavourable prognosis was found in other human malignancies [20][21][22].…”
Section: Discussionmentioning
confidence: 98%
“…High OPN expression is associated with progression, metastatic spread, and poor prognosis in many malignancies. Several studies in different human malignancies identified OPN as suitable diagnostic and prognostic biomarker [17][18][19][20][21][22][23][24]. In PCNSL, osteopontin (also known as secreted phosphoprotein 1, SPP1) is one of the most differentially up-regulated genes as compared to both nodal and extranodal non-CNS diffuse large B-cell lymphoma (DLBCL) [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In human malignant melanoma, OPN expression is significantly associated with reduced relapse-free survival and additional histological parameters that are associated with poor clinical outcome [7,24,29,33]. OPN is a prognostic marker in a variety of cancers [30,[39][40][41]. In metastatic and primary melanomas, OPN has also been suggested to be a novel promising biomarker for the detection of metastases in patients with primary melanomas [24,[42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%